The Corporate Social Responsibility (CSR) Practice of Environmental Sensitive Companies and Its Impacts on Corporate Financial Performance (CFP) - Ho, Jie Min (Curtin University, 2017)
The objective of the study is to determine the relationship between CSR and CFP of the Malaysian environmental sensitive companies, based on the legitimacy theory. The study analysed 205 sample companies for the period of 2015, using secondary data and applied hierarchical multiple regression model. The results show that companies displaying greater CSR behavior are associated with higher CFP. That is to say, there is a positive relationship between CSR and CFP.